2010
DOI: 10.1186/1751-0147-52-23
|View full text |Cite
|
Sign up to set email alerts
|

Field experience with two different vaccination strategies aiming to control infections with Actinobacillus pleuropneumoniae in a fattening pig herd

Abstract: BackgroundThe prevalence of pleurisies recorded at slaughter is increasing in Sweden, and acute outbreaks of actinobacillosis that require antimicrobial treatments have become more frequent. As an increased use of antimicrobials may result in the development of antimicrobial resistance it is essential to develop alternative measures to control the disease. Vaccinations present an appealing alternative to antimicrobial treatments. The aim of this work was to evaluate the potential of two different vaccination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…However, serotype 6 is present in 26% of SPF herds, serotype 2 in 17%, serotype 7 in 0.4%, and serotype 5 in 0.1% (5). Studies have shown that vaccines against APP can reduce the prevalence of pleuritis (16, 17). Vaccines against APP are the third most frequently used type of vaccines in Danish pig production, representing 8% of the vaccine dosages prescribed in 2013 (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, serotype 6 is present in 26% of SPF herds, serotype 2 in 17%, serotype 7 in 0.4%, and serotype 5 in 0.1% (5). Studies have shown that vaccines against APP can reduce the prevalence of pleuritis (16, 17). Vaccines against APP are the third most frequently used type of vaccines in Danish pig production, representing 8% of the vaccine dosages prescribed in 2013 (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, attenuated mutant vaccine candidates have been shown to provide a partial cross-protection and reduced morbidity ( Tonpitak et al, 2002 ; Maas et al, 2006 ). So far, DNA vaccines ( Chiang et al, 2009 ; Lu et al, 2011 ), subunit vaccines ( Sjolund and Wallgren, 2010 ; Lopez-Bermudez et al, 2014 ), recombinant subunit vaccines ( Jirawattanapong et al, 2008 ; Oldfield et al, 2008 , 2009 ; Shao et al, 2010 ; Sadilkova et al, 2012 ; Seo et al, 2013 ; Park et al, 2015 ; Li et al, 2016 ), ghost vaccine ( Katinger et al, 1999 ; Hensel et al, 2000 ), and live vector vaccine ( Shin et al, 2013 ; Hur and Lee, 2014 ) for APP had been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with a vaccination strategy appears to be a low cross-immunity between serotypes (Higgins et al 1985;Fenwick and Henry 1994). In addition, modern subunit or toxoid vaccines do not provide full protection against the clinical outbreak of the disease (e.g., reduction in mortality, increase in daily weight gain, amounts of condemnations for pneumonia) (Chiers et al 1998;Sjölund and Wallgren 2010;Jirawattanapong et al 2010;Del Pozo Sacristan et al 2014). Thus, antibiotics still prevail as the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%